Kinematic predictors of single-leg squat performance: a comparison of experienced physiotherapists and student physiotherapists - Weeks Benjamin K; Carty Christopher P; Horan Sean A (BMC Musculoskeletal Disorders, 2012)
Abstract Background The single-leg squat (SLS) is a common test used by clinicians for the musculoskeletal assessment of the lower limb. The aim of the current study was to reveal the kinematic parameters used by experienced and inexperienced clinicians to determine SLS performance and establish reliability of such assessment. Methods Twenty-two healthy, young adults (23.8 ± 3.1 years) performed three SLSs on each leg whilst being videoed. Three-dimensional data for the hip and knee was recorded using a 10-camera optical motion analysis system (Vicon, Oxford, UK). SLS performance was rated from video data using a 10-point ordinal scale by experienced musculoskeletal physiotherapists and student physiotherapists. All ratings were undertaken a second time at least two weeks after the first by the same raters. Stepwise multiple regression analysis was performed to determine kinematic predictors of SLS performance scores and inter- and intra-rater reliability were determined using a two-way mixed model to generate intra-class correlation coefficients (ICC3,1) of consistency. Results One SLS per leg for each participant was used for analysis, providing 44 SLSs in total. Eight experienced physiotherapists and eight physiotherapy students agreed to rate each SLS. Variance in physiotherapist scores was predicted by peak knee flexion, knee medio-lateral displacement, and peak hip adduction (R2 = 0.64, p = 0.01), while variance in student scores was predicted only by peak knee flexion, and knee medio-lateral displacement (R2 = 0.57, p = 0.01). Inter-rater reliability was good for physiotherapists (ICC3,1 = 0.71) and students (ICC3,1 = 0.60), whilst intra-rater reliability was excellent for physiotherapists (ICC3,1 = 0.81) and good for students (ICC3,1 = 0.71). Conclusion Physiotherapists and students are both capable of reliable assessment of SLS performance. Physiotherapist assessments, however, bear stronger relationships to lower limb kinematics and are more sensitive to hip joint motion than student assessments.